Opłaty ekologiczne w polskim systemie finansowania ochrony środowiska - Bartniczak, Bartosz (Ecological Payments in the Polish System of Financing the Environment Protection, 2005)
The article presents the position of payment for the ece using of the environment in Polish system of financing environment protection. The article shows the functions these payments fulfill. The article also presents the analysis of returns of this payment in the last five years. It also presents advantages and disadvantages of this system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (3); 2005; nr 1075, s. 13-21